Conceptualising conflicts in cyberspace. Issue 1 (2nd January 2018) - Steiger, Stefan; Harnisch, Sebastian; Zettl, Kerstin; Lohmann, Johannes
ABSTRACT: The article conceptualises political conflict in cyberspace. Thus far, scholarship has focussed on the analysis of (unilateral) cyberattacks, measuring their scope and impact, especially in Western industrialised countries. But cyber conflict, defined here as an incompatibility of stated intentions between actors which guides their use of computer technologies to harm the other, has received much less attention. Our conceptual approach builds on the work done by Valeriano and Maness and others in the field of cyber conflict measurement. We argue, however, that the interactive, international and inter-agential nature of cyber conflicts has not been captured sufficiently in recent scholarship. By providing a new methodology to address the problems of information bias, attribution and the neglect of non-state actors, we hold that variance in cyber conflict dynamics as well as spill-over effects between off- and online conflicts may be better captured with the new approach. Our work seeks to extend the understanding of state and non-state conflict behaviour in cyberspace and our methodology may inform further extensive data collections.